Chemical stability and cytotoxicity of human insulin loaded in cationic DPPC/CTA/DDAB liposomes. - Manosroi A. (2014)
Liposomes were prepared from DPPC (dipalmitoyl phosphatidyl choline) mixed with Chol (cholesterol) and CTA [cholest-5-en-3-ol(3beta)(trimethylammonio) acetate] or DDAB (dioctadecyl dimethyl ammonium bromide) at various molar ratios by chloroform film method with sonication. The most physical stable (no sedimentation with an average zeta potential value of 47.7+/-1.44 mV) liposomal formulation (DPPC/CTA/DDAB at 7:2:1 molar ratio) was selected to load with human insulin (0.45 mg/mL) by the freeze dried empty liposomes (FDELs) method with the entrapment efficiency of human insulin of 62.72% (determined by gel filtration). Liposomes were spherical shape with unilamellar structure and an average size of 2.26+/-0.87 microm determined by TEM. The percentages of insulin remaining in liposomes when stored at 4+/-2, 30+/-2 and 45+/-2 degrees C for 4 months were 26.21, 36.86 and 15.75% which were higher than human insulin solution of 6.13, 11.31 and 2.61 times, respectively. The percentages of entrapment of human insulin were 62.72 at initial and at 31.72, 64.10 and 8.10 when kept at 4+/-2, 30+/-2 and 45+/-2 degrees C, respectively, for 4 months. The synthesized cationic lipid, CTA, and the DPPC/Chol/CTA liposomes loaded with human insulin demonstrated no cytotoxicity on normal human skin fibroblast but some cytotoxic effects on mouth epidermal cancer cell line. This study has demonstrated the enhancement of chemical stability of human insulin with no cytotoxicity when loaded this protein in cationic DPPC/CTA/DDAB liposomes. The results indicated the potential application of this cationic liposomal formulation for topical therapeutic use.